Comparison of the mechanical properties of chopped glass, carbon, and aramid fiber reinforced polypropylene. (2nd June 2022) - Ari, Ali; Bayram, Ali; Karahan, Mehmet; Karagöz, Seçgin
In this work, a comparative assessment of the mechanical properties of chopped glass-carbon-aramid fiber reinforced polypropylene (PP) composites was carried out. Reinforcement and matrix materials were mixed with the extrusion method, and then composite materials were produced in the form of plates with the press molding technique. The composites' tensile, 3-point bending, and drop weight tests were carried out and the surface morphology of the fractured surfaces was examined by Scanning Electron Microscope (SEM). The tests' results indicate that the mechanical properties increase significantly in the presence of fiber. On the other hand, it is observed that the effect in percentage decreases as the fiber content increases. Moreover, It was observed that some of the fiber materials were pulled out from the matrix as a result of stress. ANOVA analysis using S/N values, and F-Test were performed to observe the effectiveness of each test factor (fiber type, and fiber additive content) on the test results. Finally, an optimization study was carried out to obtain the mathematical expression by fitting the experimental data.